Modeling the relationship between the strength of a relative age effect and the maturity level applied for selection - Lames, M. (Proceedings of the 2016 International Association of Computer Science in Sport (IACSS) Conference, 2016)
The purpose of this study is to examine the relationship between Relative Age Effect (RAE) and maturity level applied for selection. Augste and Lames (2011) gave the interpretation of a RAE as indicator of selecting according to momentary performance that in turn is determined by maturity level in youth samples. It has been shown that with a small set of assumptions one is able to model the relationship between birthday distribution and biological age applied as selection threshold (Lames & Werninger, 2012). Effect size of a RAE may be described by the median of the birthdays of the sample examined (Augste & Lames, 2011). This study models the functional relationship between the median of birthdays and the maturity level applied for selection.